EFFECTS OF PRIMING ON GERMINATION AND SEEDLING VIGOUR OF BIRD’S EYE CHILLI (CAPSICUM FRUTESCENS L.) SEEDS COLLECTED FROM EASTERN HIMALAYAN REGION OF INDIA - S. K. DUTTA; A. R SINGH; T. BOOPATHI; S. B. SINGH; M. C. SINGH; MALSAWMZUALI (The Bioscan, 2015)
A study was conducted to find out the efficacy of organic and inorganic priming on germination and seedling vigour of bird’s eye chilli (Capsicum frutescens L.) seeds collected from eastern Himalayan region of India. Results showed that, all studied traits were affected by priming treatments and there was completely significant difference (p≤0.05) in germination percentage between primed and non primed seeds. Among all priming treatments, 1% KNO3 (39.68 % higher) recorded the highest germination percentage as compared to non primed control. Other best treatments recorded were 2% KH2PO4 (37.50 % higher than control) followed by 200g/Kg seed neem leaf powder (NLP) (35.12 % higher than control) and 3% KNO3 (35.12 % higher than control). In addition to this, 200g/Kg seed NLP treatment recorded lowest mean germination time (13.53 days) while control recorded maximum mean germination time (21.63 days). From the study it was concluded that, seed treatment with NLP is essential for pre and post storage treatment of seeds, as it maintained seed viability and seedling vigour optimally among all other treatments.